1985
DOI: 10.1038/ki.1985.2
|View full text |Cite
|
Sign up to set email alerts
|

Proximal tubule dopamine histofluorescence in renal slices incubated with L -dopa

Abstract: Renal cortex slices were incubated with amine precursors L-dopa, or L-5-HTP. Localization of synthesized amines, dopamine or serotonin, was examined by means of histofluorescence methods. Formaldehyde-induced fluorescence was present in the proximal convoluted tubule and not in the pars recta or other segments of the tubules after incubation in the presence of 10(-3) to 10(-7) M L-dopa. Tubule-induced fluorescence was not seen in the presence of an inhibitor of dopa-decarboxylase or in the absence of sodium. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(27 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…This may be due to high intrarenal concentrations of dopamine overcoming the DA1-receptor antagonism in a competitive manner with time. This may occur preferentially at the proximal tubular receptors (Felder et al, 1984) close to the site at which dopamine is thought to be generated (Hagege & Richet, 1985) and secreted (Baines & Chan, 1980). Serum sulpiride concentrations were falling throughout the gludopa infusion and may have contributed to an increasing effect of gludopa.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to high intrarenal concentrations of dopamine overcoming the DA1-receptor antagonism in a competitive manner with time. This may occur preferentially at the proximal tubular receptors (Felder et al, 1984) close to the site at which dopamine is thought to be generated (Hagege & Richet, 1985) and secreted (Baines & Chan, 1980). Serum sulpiride concentrations were falling throughout the gludopa infusion and may have contributed to an increasing effect of gludopa.…”
Section: Discussionmentioning
confidence: 99%
“…The basis of its relative renal specificity lies in the sequential conversion to dopamine by the actions of y-glutamyl transfer- (Hagege & Richet, 1985) and there is much evidence to suggest that urine dopamine is principally derived, under normal conditions, from the uptake and decarboxylation of circulating Ldopa in proximal tubular cells (Lee, 1986). Worth et al (1985) have previously demonstrated that gludopa increases renal blood flow and glomerular filtration rate with a small reduction in filtration fraction.…”
Section: Discussionmentioning
confidence: 99%
“…In these previous studies therefore a reduction in the inhibitory effect of All on dopamine excretion might have offset the effect of reduced natriuresis. All is known to act on the proximal tubule to stimulate sodium resorption (Navar et al, 1987) and it is known that this is the site of renal dopamine formation (Hagege & Richet, 1985). Dopamine decreases sodium resorption in the pars recta of the proximal tubule (Bello- Reuss et al, 1982) by acting on specific receptors (Felder et al, 1984) so an inhibitory effect of AII on dopamine excretion at this site is feasible.…”
Section: Discussionmentioning
confidence: 99%